SPE Middle East Oil and Gas Show and Conference 2013
DOI: 10.2118/164331-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of LoSal™ on Oil Recovery from a Selected Carbonate Reservoir in Abu Dhabi-An Experimental Approach

Abstract: Low-salinity water flooding LoSal™ has been used to improve oil recovery for many decades. Historically, the physical mechanism behind this improvement in oil recovery was attributed to the pressure maintenance and displacement of oil by injected water. Recently, evidence from laboratory and field tests indicated that water flooding also involves chemical processes and that modifying of the injection brine salinity and its ionic composition can significantly impact the oil recovery. Several theories regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Secondary mode 10-fold diluted sea water injection recovered 10% additional oil compared to the sea water injection in secondary mode. Similar results have been reported by other researchers all indicating improved oil recovery by low salinity injection in carbonate rocks, either by diluting the high salinity brine or by manipulation of the determining ions in the injected brine (Zahid et al, 2012, Romanuka et al, 2012, Al-Attar et al, 2013, and Al-Shalabi et al, 2013.…”
Section: Low Salinity Injection In Carbonatessupporting
confidence: 84%
“…Secondary mode 10-fold diluted sea water injection recovered 10% additional oil compared to the sea water injection in secondary mode. Similar results have been reported by other researchers all indicating improved oil recovery by low salinity injection in carbonate rocks, either by diluting the high salinity brine or by manipulation of the determining ions in the injected brine (Zahid et al, 2012, Romanuka et al, 2012, Al-Attar et al, 2013, and Al-Shalabi et al, 2013.…”
Section: Low Salinity Injection In Carbonatessupporting
confidence: 84%
“…The trends in IFT values observed in this study are similar to the one observed for a pure alkane−brine system in our previous study. 34 Al-Attar et al 35,36 have reported crude oil−seawater IFT values for crude oil from the Bu Hasa oilfield and seawater from Arabian Gulf (40 980 ppm). They have observed a continuous increase in IFT with brine dilution.…”
Section: Resultsmentioning
confidence: 99%
“…However, the affinity of Mg 2+ ions increases with the temperature; and they can substitute Ca 2+ ions from the carbonate lattice [17][18][19]23]. It is reported that increasing the concentration of Ca 2+ ions resulted in a decreased ultimate recovery during core flooding experiments [44]. SO 4 2− ions are reported in literature as strong PDIs towards carbonate surfaces.…”
Section: Individual Effect Of the Potential Determining Ionsmentioning
confidence: 99%